EFFects of exposure and cognitive behavioral therapy for chronic BACK pain (“EFFECT-BACK”): study protocol for a randomized controlled trial - Vogt, Rabea; Haas, Julia; Baumann, Lukas; Sander, Anja; Klose, Christina; Riecke, Jenny; Rief, Winfried; Bingel, Ulrike; Maser, Dustin; Witthöft, Michael; Keßler, Jens; Zugaj, Marco; et al. (Trials, 2024)
Introduction: Chronic back pain is a widespread medical condition associated with high socioeconomic costs and increasing prevalence. Despite the advanced implementation of multidisciplinary approaches, providing a satisfactory treatment offer for those affected is often not possible. Exposure therapy (EXP) promises to be an effective and economical form of treatment and in a previous pilot study showed to be superior to cognitive behavioral therapy (CBT) in reducing perceived limitations of movement. The current study aims to further compare the efficacy of both treatment methods and identify those patient groups that particularly benefit from EXP. Methods: The general objective of this randomized multicenter clinical trial (targeted N = 380) is to improve and expand the range of treatments available to patients with chronic back pain. As the primary objective of the study, two different psychological treatments (EXP and CBT) will be compared. The primary outcome measure is a clinically significant improvement in pain-related impairment, measured by the QPBDS, from baseline to 6-month follow-up. Secondary outcome measures are absolute changes and clinically significant improvements in variables coping, psychological flexibility, depressiveness, catastrophizing, exercise avoidance and fear of exercise, and intensity of pain. Participants are recruited in five psychological and medical centers in Germany and receive ten sessions of manualized therapy by trained licensed CBT therapists or clinical psychologists, who are currently in their post-gradual CBT training. Potential predictors of each treatment’s efficacy will be explored with a focus on avoidance and coping behavior. Conclusion: This study will be the first RCT to compare CBT and EXP in chronic back pain in a large sample, including patients from different care structures due to psychological and medical recruitment centers. By identifying and exploring potential predictors of symptom improvement in each treatment group, this study will contribute to enable a more individualized assignment to treatment modalities and thus improves the care situation for chronic back pain and helps to create a customized treatment program for subgroups of pain patients. If our findings confirm EXP to be an efficacious and efficient treatment concept, it should gain more attention and be further disseminated. Trial registration: ClinicalTrials.gov NCT05294081. Registered on 02 March 2022.
Gesehen am 16.08.2024